Evaluation of UASB Reactor Performance During Start-Up Operation Using Glucose Bearing Synthetic Wastewater - Subramanyam, Revanuru (International Journal of Environment, 2020)
This research article describes start-up performance of an UASB (Upflow Anaerobic Sludge Blanket) reactor in terms of chemical oxygen demand (COD) removal efficiency, biogas production, sludge loading rate (SLR), volatile fatty acids (VFA), pH, alkalinity, total solids (TS) and volatile suspended solids (VSS), fed with synthetic wastewater with increased concentrations of glucose. The reactor was loaded up to an OLR (Organic Loading Rate) of 15 kg COD m-3 d-1 and achieved a COD removal efficiency of 82 ±3%. The results showed that digested seed sludge was successfully acclimatized and transformed finally into granular sludge within a period of 120 days. An increase in the accumulation of VFA at high OLRs showed that methanogenesis could be the rate-limiting step in the reactor operation. The SLR and VSS/TS ratio were increased with an increase in OLR. During the initial stages, uniform distribution of VSS concentration and later on maximum VSS concentration were found at port number two at a height of 350 mm. The carbon balance depicts that the maximum percentage of influent COD converted to methane COD. An increase in specific methanogenic activity values with the age of sludge confirmed the transformation of the seed sludge in to a granular sludge.